2023
DOI: 10.1155/2023/4864334
|View full text |Cite
|
Sign up to set email alerts
|

Novel Soliton Solutions for the (3 + 1)-Dimensional Sakovich Equation Using Different Analytical Methods

Abstract: In the work that we are doing now, our goal is to find a solution to the (3 + 1)-dimensional Sakovich equation, which is an equation that can be used to characterize the movement of nonlinear waves. This approach sees extensive use across the board in engineering’s many subfields. This new equation can represent more dispersion and nonlinear effects, which allows it to accept more different application scenarios. As a result, it has a wider range of potential applications in the physical world. As a consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…In this article, seven different types of solutions originated via the GERFM. The applied solutions differ from the results obtained through previously employed methods [25][26][27]. The physical characteristics of the generated solutions have been examined through graphical representations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, seven different types of solutions originated via the GERFM. The applied solutions differ from the results obtained through previously employed methods [25][26][27]. The physical characteristics of the generated solutions have been examined through graphical representations.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-soliton analysis of Equation ( 3) was conducted, and its integrability was assessed using the Painlevé test [25]. Ali et al [26] utilized the G ′ /(bG ′ + G + a)-expansion and exp(-ψ(ξ)) procedure to identify analytical solutions for the equation. Cortez et al identified Lie symmetries of Equation ( 3) [27].…”
Section: Introductionmentioning
confidence: 99%